Femtosecond laser controlled wettability of solid surfaces. Issue 46 (29th September 2015) - Yong, Jiale; Chen, Feng; Yang, Qing; Hou, Xun
Abstract : This paper introduces four typical aspects of femtosecond laser induced special wettability: superhydrophobicity, underwater superoleophobicity, anisotropic wettability, and smart wettability. Abstract : Femtosecond laser microfabrication is emerging as a hot tool for controlling the wettability of solid surfaces. This paper introduces four typical aspects of femtosecond laser induced special wettability: superhydrophobicity, underwater superoleophobicity, anisotropic wettability, and smart wettability. The static properties are characterized by the contact angle measurement, while the dynamic features are investigated by the sliding behavior of a liquid droplet. Using different materials and machining methods results in different rough microstructures, patterns, and even chemistry on the solid substrates. So, various beautiful wettabilities can be realized because wettability is mainly dependent on the surface topography and chemical composition. The distinctions of the underlying formation mechanism of these wettabilities are also described in detail.